BER Performance Improvement of Dual Chaotic Maps Based on STBC Communication System - Abdulameer , Lwaa Faisal; Sripati, U.; Kulkarni, Muralidhar (Al-Khwarizmi Engineering Journal, 2022)
Sensitive information of any multimedia must be encrypted before transmission. The dual chaotic algorithm is a good option to encrypt sensitive information by using different parameters and different initial conditions for two chaotic maps. A dual chaotic framework creates a complex chaotic trajectory to prevent the illegal use of information from eavesdroppers. Limited precisions of a single chaotic map cause a degradation in the dynamical behavior of the communication system. To overcome this degradation issue in, a novel form of dual chaos map algorithm is analyzed. To maintain the stability of the dynamical system, the Lyapunov Exponent (LE) is determined for the single and dual maps. In this paper, the LE of the single and dual maps have been computed numerically. Increasing the dynamical behavior of the system by using more complex chaotic maps leads to inferiority in the overall system performance. So, in this work, the BER performance for the dual and single chaotic maps by exploiting the benefits of a hybrid Chaos Shift Keying-Multiple-Input-Multiple-Output (CSK-MIMO) communication system has been investigated. The results show that the dual tent map has more randomness, whereas the single logistic map has the least randomness. As well as the CSK-MIMO gives an outstanding BER performance when it compared with the SISO system which helps in reducing the system’s inferiority.